ALTERITIES OF SIGHT. BENCHMARKS OF MEDIATIC RE-VIEWING THE READING OF REALITY. - ILEA, Mihaiela (REVART: Specialized Review of Theory & Critique of Arts, 2017)
Television and new media construct a type of trade with the iconic sign. To the image is assigned an effervescent power, so that it can, under the pretext of illustrating, create a new perspective of the information-formation-seduction triad. The subjectivity of the image, caught between the liberty of re-seeing the collective show of society and the responsibility of sight, can only be overcome through keeping a balance between the one who proposes the typology of the message (the journalist) and the one who is decoding it (the viewer). The two are united by the experience of seeing the same sample of reality and are separated by the role of phenomenology of communication means and the reception of visual language.